Upaya Peningkatan Aktivitas dan Prestasi Belajar Pendidikan Agama Hindu Melalui Penerapan Cooperative Learning Tipe Group Investigation (GI) - Ida I Dewa Ayu Ketut Putri (Jurnal Penjaminan Mutu, 2015)
Cooperative learning : group investigation (GI) is a learning strategy to determine the student’s development and progress that oriented to class activities and allow students to use a variety of learning resources besides teachers. The low learning achievement obtained by students in particular on the subjects of Hinduism is noteworthy. It is caused by several factors, including the intelligence of students, student motivation, interest in learning, study habits, as well as external factors such as student living environment, the infrastructure that supports the learning process inadequate. To see whether the implementation of Cooperative Learning type Group Investigation able to improve student learning outcomes, this study applied the model to the 2nd year student (class F) in SMP Negeri 3 Denpasar school year 2011/2012. This study was classified as a class action (classroom action reseach) which is the subject is the 2nd year student (class F) as many as 28 people and the object of research is the student’s learning activities. This study used primary data obtained directly from the students by using the technique of testing and observation sheet. The collected data were analyzed descriptively based on the average and standard deviation that obtained through the results of the evaluation scores at each end of the cycle. The results showed a very significant increase in activity of students from an average score of 2.93 in the first cycle to 4.14 in the second cycle. The average student achievement in the first cycle is 70.64 with classical completeness of 60% increased to 75.54 with classical completeness of 92.9%.